Implementasi Pengiriman Data Multi-Node Sensor Menggunakan Metode Master-slave pada Komunikasi LoRa - Agiya Yoshua; Rakhmadhany Primananda; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Wireless technology has begun to develop and connect with each other, so this is what makes a basis for the development of the Internet of Thing technology or abbreviated as IoT. There are several elements in helping the performance of IoT technology, one of which is in terms of communication. LoRa is a wireless transmission communication technology using Chirp Spread Spectrum (CSS) as a modulation technique of its delivery. LoRa uses Pure ALOHA as an access method for sending data where two or more nodes send data at the gateway without coordinating with each other, causing the risk of data collisions. In this study using the master-slave method to send data to avoid data collisions. Gateway node acts as a master whose job is to send data request messages to the sensor node. The sensor node acts as a slave whose duty is to send sensor data to the gateway node that acts as the master only if the master requests the sensor node specifically based on the slave ID that the sensor node has. Functionality and non-functional tests are carried out to test whether the system is operating properly. The smallest percentage of packet loss is experienced under test conditions at a distance of 50 meters where packet loss only occurs in the process of sending from sensor node 1 to the gateway, while the largest percentage of packet loss is experienced under test conditions at a distance of 200 meters on a 30 minute test duration of 8.99% . The smallest average delay test results are experienced in testing conditions at a distance of 200 meters with an average delay of up to 160.64 milliseconds, while the largest is experienced at a distance of 100 meters with an average delay of up to 405.67 milliseconds.